LOCUS OF CONTROL VOCATIONAL SCHOOL STUDENTS IN CAREER PLANNING - Yuni Agustina; A. Muri Yusuf Yusuf; Afdal (Yayasan Citra Dharma Cindekia, 2021)
This article aims to describe the locus of control of SMK students in career planning. Career planning is very important for students because after graduating from school they will determine where and what career choices will be taken. The phenomenon that occurs at this time regarding the locus of control of vocational students in career planning is the lack of students in determining a decision about their future, students lack time management and study well at school. Most students do not have good ideas and do not develop skills in career planning. The research method of this article is a literature review analysis (literature research) this article will describe the analysis of scientific journals that are relevant to the discussion that has been selected, while the stages in this research method are (1) selecting articles, (2) collecting initial data, (3) challenge the topic, (4) collect supporting data, (5) make conclusions and recommendations online. The results of this article are that many students will complete their formal education in senior high school and the efforts that need to be taken so that all students get career guidance opportunities so that students mature in planning their careers